Pengaruh Stabilisasi Tanah Bekas Tambang Menggunakan Fly Ash dan Kapur Terhadap Parameter Kuat Geser - Fathurrahman Al Mudzakki; Syahril Rahmat; Nevy Sandra; Oktaviani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The ex-mining land in Gunung Sarik, Padang City, has soil conditions with low shear strength due to structural degradation resulting from mining activities. This study aims to analyze the effect of stabilization using fly ash (Class F) and quicklime on the improvement of soil shear strength parameters (cohesion c and internal friction angle φ), with a specific focus on the effect of lime content variations (0%, 4%, 8%, 12%) at a constant fly ash content of 5%. The research methods included soil physical properties testing (moisture content, specific gravity, sieve analysis, Atterberg limits) and direct shear testing referring to ASTM/SNI standards. Based on the Unified Soil Classification System (USCS), the soil was classified as high-plasticity gravelly elastic silt (MH) with a water content of 24.91% and a plasticity index of 15.71%. At 5% fly ash content, the addition of lime increased the cohesion value from 0.049 kg/cm² (0% lime) to 0.234 kg/cm² (8% lime) and the internal friction angle from 43.45° to 67.26°. However, at 12% lime addition, the cohesion value decreased to 0.140 kg/cm², while the internal friction angle increased to 76.77°. The increase in shear strength occurred due to the pozzolanic reaction between CaO from lime and SiO₂ and Al₂O₃ from fly ash, which formed cementitious compounds that bind soil particles. The optimum combination was obtained at a mixture of 5% fly ash + 8% lime. This study recommends the use of this combination for subgrade improvement in light to medium construction in ex-mining areas.